The Role of Genetic Testing in the Evaluation of Dilated Cardiomyopathies - Kolade M. Agboola; Trevon McGill; Barry A. Boilson; Naveen L. Pereira; Jacob C. Jentzer (Case Reports in Cardiology)
We present an adolescent African American male admitted to the cardiac intensive care unit with cardiogenic shock and acute respiratory failure. Through an overview of his presentation, diagnostic workup, and treatment, we demonstrate the clinical utility of genetic testing in the evaluation of unexplained dilated cardiomyopathies.